Decreased performance of live attenuated, oral rotavirus vaccines in low-income settings: causes and contributing factors. (1st February 2018) - Velasquez, Daniel E.; Parashar, Umesh; Jiang, Baoming
ABSTRACT: Introduction : Numerous studies have shown that the oral rotavirus vaccines are less effective in infants born in low income countries compared to those born in developed countries. Identifying the specific factors in developing countries that decrease and/or compromise the protection that rotavirus vaccines offer, could lead to a path for designing new strategies for the vaccines' improvement. Areas covered : We accessed PubMed to identify rotavirus vaccine performance studies (i.e., efficacy, effectiveness and immunogenicity) and correlated performance with several risk factors. Here, we review the factors that might contribute to the low vaccine efficacy, including passive transfer of maternal rotavirus antibodies, rotavirus seasonality, oral polio vaccine (OPV) administered concurrently, microbiome composition and concomitant enteric pathogens, malnutrition, environmental enteropathy, HIV, and histo blood group antigens. Expert commentary : We highlight two major factors that compromise rotavirus vaccines' efficacy: the passive transfer of rotavirus IgG antibodies to infants and the  co-administration of rotavirus vaccines with OPV. We also identify other potential risk factors that require further research because the data about their interference with the efficacy of rotavirus vaccines are inconclusive and at times conflicting.